What can mixed-species flock movement tell us about the value of Amazonian secondary forests? Insights from spatial behavior - Mokross, Karl [UNESP]; Potts, Jonathan R.; Rutt, Cameron L.; Stouffer, Philip C. (Wiley-Blackwell, 2018)
The value of secondary forest for rain forest species remains an important question for conservation in the 21st century. Here, we describe the spatial behavior of understory mixed-species flocks in a heterogeneous landscape in central Amazonia. Understory mixed-species flocks represent a diverse, highly organized component of the rich Amazonian avifauna. We recorded movements within 26 flock home ranges in primary forest, secondary forest, interfaces between forest types, and forest fragments. We describe frequency and movement orientation in relation to forest edges, movement patterns and proportion of use between secondary and primary forest, the relation between home range sizes and vegetation height, and home range configuration. Flocks visited only a small portion of forest edges, and showed a tendency for moving parallel to edges next to less-developed secondary forest. Movement patterns in secondary forests did not show significant differences compared to primary forests. Time spent in secondary forests increased in proportion to mean canopy height. Flocks were consistently present in secondary forests where vegetation height averaged over 15m, but home ranges were nearly twice as large compared to primary forest. Home range limits tended to be aligned with disturbed vegetation, essentially rearranging a territorial configuration normally adjusted by topography. The spatial behavior of this important subset of the Amazonian avifauna shows that secondary forests are tolerated above a certain development threshold, but perceived as suboptimal habitat until canopy height closely matches primary forests. RESUMO O valor de florestas secundarias para especies florestais continua sendo uma importante questAo na conservacAo de ecossistemas tropicais no seculo XXI. Aqui, descrevemos o comportamento espacial de bandos mistos de sub-bosque em uma paisagem heterogenea na Amazonia central. Registramos os movimentos em 26 areas de vidas de bandos em floresta primaria, floresta secundaria, interfaces entre ambas e fragmentos florestais. Descrevemos a frequencia de uso e orientacAo em relacAo a bordas florestais, e padroes predominantes de movimento, proporcoes de uso entre floresta primaria e secundaria, relacAo entre tamanho de areas de vida em relacAo a altura da vegetacAo, e configuracAo territorial em paisagens heterogeneas. Resultados mostram uma pequenos trechos de bordas florestais sendo visitadas e uma tendencia de movimento paralelo a borda quando proximas a capoeiras pouco desenvolvidas. NAo foram detectadas diferencas significativas em padroes de movimento entre florestas primarias e secundarias. Tempo passado em florestas secundarias aumentou proporcionalmente com a altura media da vegetacAo. Bandos foram detectados consistentemente em florestas secundarias apos estas atingirem alturas medias maiores que 15m, mas areas de vida eram quase o dobro da area de bandos em floresta primaria. Houve uma correlacAo negativa entre altura media da vegetacAo e tamanho da area de vida. Limites de areas de vida tendiam estar alinhados a vegetacAo degradada, essencialmente reorganizando configuracAo territorial normalmente ajustada por topografia. O comportamento espacial deste importante subconjunto da avifauna amazonica mostra que florestas secundarias sAo toleradas acima de um certo limite de desenvolvimento, mas sAo percebidas como habitat subotimo ate que a altura media da vegetacAo alcance estatura proxima de florestas primarias.
Keywords: Amazon; animal movement; biological dynamics of forest fragments project; forest fragmentation; heterogeneous landscapes; mixed-species flocks; secondary forests